Exploratory research into energy efficiency investment and strategy - Fresner, Johannes; Krenn, Christina; Kleshchov, Anton; Tomasi, Fabio (Technology audit and production reserves, 2018)
The object of research is the process of implementing energy-efficient measures at industrial enterprises. One of the problem is the trend of reduction of investment in the sphere of energy efficiency. It has been established that after several years of growth, global investments in energy efficiency and renewable energy sources began to decline in 2017. According to the International Energy Agency, there is a risk that the trend of investment shrinkage will continue. In the framework of the PINE project in Austria, 20 energy audits were carried out, which resulted in the introduction of measures aimed at energy efficiency. According to the results of the project, the link between investment and implementation of measures on energy efficiency and life cycle and type of enterprises implemented in companies of different industries was analyzed and argued. It is established that about 50 % of the identified energy savings from the implementation of measures is the result of the use of frequency drive drives, elimination of leakage of compressed air or modernization of lighting systems. This allows to develop rational business and policy strategies for enterprises at different stages of the life cycle. In the course of the study, an approach focused on single operations selected in this program has been analyzed, which facilitates the identification of links between energy consumption by production units and technological and organizational factors influencing its consumption. The scientific novelty of the research is expressed in the substantiation of critical strategic barriers in the field of investment in energy-efficient solutions, which allowed proposing rational business strategies and appropriate political support measures to overcome them. Due to the fact that enterprises with the same input and output resources can have a different process cycle, payback periods for the same implemented measures may be different. An analysis of the real experience of energy conservation with the developed business strategies and policies of political support allows it to be effectively disseminated in European countries.